Scrupulosity in Obsessive-Compulsive Disorder Patients: A Systematic Literature Review and Bibliometric Analysis from 2000 to 2023 - Sharma, Ankuna; Lone, Dr. Zahoor Ahmad; Singh, Aarti (Journal of Neonatal Surgery, 2025)
Scrupulosity is the most common psychological disorder among OCD sufferers nowadays. There is a lack of information and stigma associated with discussing religious obsession and mental health difficulties, cultural disparities, and understanding of OCD among healthcare practitioners and the general population. Purpose: This review article attempts to condense many studies into a single document by doing a bibliometric evaluation of wide and diverse information on scrupulosity in OCD patients. It also outlines future studies and explains how the research has grown and progressed. Design: The study builds on the systematic review approach with bibliometric analysis, for which the R software package Biblioshiny was investigated. It was carried out using techniques like thematic mapping, citation evaluation, key keyword co-occurrence, and co-citation analysis. Findings: The research highlighted the most significant authors, journals, studies, and nations in the discipline of scrupulosity in OCD research amongst the most widely cited writers, as determined by a bibliometric data assessment of 54 works extracted from the Scopus database between 2000 and 2023. The paper states that experts' interest in scrupulosity in OCD rose in 2004, 2006, and 2009. Inozu M., Abramowitz JS, Ferugus TA, and Clark DA were the writers who contributed the most to scrupulosity in OCD papers. The results can assist researchers in the future in establishing a starting point before focusing on studies in this field. Value: The fast growth of these psychoneurotic disorder articles in recent years has demanded a thorough evaluation of the research on this subject. To proceed with this topic, multiple scientists have publicised review articles on scrupulosity in OCD from diverse viewpoints. Nonetheless, no publications with bibliometric analyses of scrupulosity in OCD have been published. It is one of the first known scientific projects on mental disorders to be evaluated